Elevated non-esterified fatty acid concentrations during bovine oocyte maturation compromise early embryo physiology. - Veerle Van Hoeck; Roger G Sturmey; Pablo Bermejo-Alvarez; Dimitrios Rizos; Alfonso Gutierrez-Adan; Henry J Leese; Peter E J Bols; Jo L M R Leroy (PLoS ONE, 2011)
Elevated concentrations of serum non-esterified fatty acids (NEFA), associated with maternal disorders such as obesity and type II diabetes, alter the ovarian follicular micro-environment and have been associated with subfertility arising from reduced oocyte developmental competence. We have asked whether elevated NEFA concentrations during oocyte maturation affect the development and physiology of zygotes formed from such oocytes, using the cow as a model. The zygotes were grown to blastocysts, which were evaluated for their quality in terms of cell number, apoptosis, expression of key genes, amino acid turnover and oxidative metabolism. Oocyte maturation under elevated NEFA concentrations resulted in blastocysts with significantly lower cell number, increased apoptotic cell ratio and altered mRNA abundance of DNMT3A, IGF2R and SLC2A1. In addition, the blastocysts displayed reduced oxygen, pyruvate and glucose consumption, up-regulated lactate consumption and higher amino acid metabolism. These data indicate that exposure of maturing oocytes to elevated NEFA concentrations has a negative impact on fertility not only through a reduction in oocyte developmental capacity but through compromised early embryo quality, viability and metabolism.